Management Factors for COVID-19 Confirmed Patients in Public Hospitals - Akbar Wahdana, Rayhan; Assa, Inriyanti; Asriati, Asriati (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction:  The management of patients confirmed positive for COVID-19 is a guideline for actions in handling people who are confirmed positive for COVID-19 through SWAB PCR examination according to their severity. Objective: The purpose of the study was to determine the management factors of COVID-19 confirmed patients at Merauke District Hospital. Method: Quantitative research with cross-sectional design. The research location is at the Regional General Hospital of Merauke Regency. Result and Discussion: The results  of the study were that women were the most dominant (87.6%) in carrying out the management of COVID-19 confirmed patients with early adulthood age of 26-35 years (73.4%) and had a new working period of <6 years (37.2%). The ability of human resources in the Merauke District General Hospital is mostly (61%) in the good category and excessive workload (71.4%). The management facilities for COVID-19 confirmed patients at the Merauke Regency General Hospital met the guideline requirements (72.4%). Conclusion: The test results of the study showed that there was a relationship between facilities (p = 0.033; PR:2,970) with the management of patients confirmed with COVID-19. However, there was no relationship between the ability of health human resources (p = 0.763; PR:1.168), and workload (p=0.149; PR:2,116) with the management of patients confirmed with COVID-19 at the Merauke Regional General Hospital.